Identificação documental em arquivos pessoais: possibilidades, convergências e desafios - Fonseca, Gabrieli Aparecida da [UNESP] (2017)
The present dissertation deals with Archival Identification in Personal Papers, through the analysis of the specific situation in this file type, especially with regard to documentary production and recovery of principle of provenance. Thus, we seek to trace a brief history, conceptualization and analysis of Archival Identification indicated in the national and international literature, based on the research of Brazil and Spain. Also points up the relationship between the Archival Identification and the principles, functions and methods of Archival Science. Turning specifically to the case of personal papers, which have a remarkable difference in their composition. Thus, it is proposed to reflect the issues surrounding personal papers. It is thus a theoretical research that has as object the personal papers, following the Total Archives approach, which comprises the integration of the files and documentary treatment. It is thus possible to see how the theory is important in the development of practice, considering that design differences can result in different specific effects. In this sense, it is expected that the critical analysis grounded in theoretical basis of different understandings of Archival Identification and establishment of the Personal Papers can potentially contribute to the development of Archival science while science, including by making possible greater concreteness to practical application of archival doings.